Complete laparoscopic wedge resection of a giant locally advanced gastric GIST with near pathological complete response after preoperative treatment with imatinib mesylate: A case report. (January 2022) - Guo, Honghai; Li, Yong; Wang, Dong; Tan, Bibo; Yang, Peigang; Zhao, Qun
Abstract: Introduction and importance: Surgical resection is the only curative treatment for gastrointestinal stromal tumor (GIST). Laparoscopic approach for large (>5 cm) and giant (>10 cm) gastric GIST remains under controversy. What's more, whether laparoscopic surgery could be performed after preoperative imatinib treatment of giant gastric GIST is still unknown. Case presentation: We report a 68-year-old man with a giant (almost 30 cm) locally advanced gastric GIST which required resection of contiguous organs initially. After received 12 months imatinib therapy, the tumor became resectable and he finally achieved a complete laparoscopic wedge resection. Pathological evaluation of the resected specimen revealed a near pathological complete response was obtained. The imatinib treatment was ongoing after surgical resection and there was no radiological or clinical evidence of disease recurrence until to October 2021. Clinical discussion: Laparoscopic approach is safe and effective for gastric GIST. Even for lesions greater for 5 cm. However, there are few reports for the application of laparoscopic wedge resection for gastric GIST larger than 10 cm. Preoperative use of imatinib can decrease the tumor size, so that may increase the chance of laparoscopic approach. Conclusion: Preoperative imatinib therapy was effective for reducing the gastric GIST, which may increase the chance of minimally invasive approach and organ preservation. Patients with locally advanced GIST could benefit from the multidisciplinary approach. Highlights: A man with a giant (almost 30 cm) locally advanced gastric GIST achieved a complete laparoscopic wedge resection with preoperative imatinib therapy. Pathological evaluation of the resected specimen revealed a near pathological complete response was obtained. Preoperative imatinib therapy may facilitate R0 resection, organ preservation and increase the chance of minimally invasive approach. Multidisciplinary approach is the optimal treatment for patients with locally advanced GIST.